Aerodynamics of High-Speed Trains with Respect to Ground Simulation - Dennis Weidner; Daniel Stoll; Timo Kuthada; Andreas Wagner (Fluids, 2022)
Wind tunnel testing is commonly used to assess and optimize the aerodynamic characteristics of high-speed trains. The train model is usually mounted above a static ground plane, but a moving ground is necessary for the correct representation of the relative motion between train and ground. This study focuses on the effect of the applied ground simulation on the aerodynamics of a high-speed train. Wind tunnel tests using a stationary and a moving ground were carried out using a 1:20 scale model of a high-speed train’s first car. Numerical simulations for two moving ground configurations are created, and the simulation setup is validated using surface pressure measurements from the wind tunnel tests. It is shown that the ground simulation has a significant effect on the drag in the considered yaw angle range. Additionally, the change in drag due to bogie fairings is evaluated and an impact of the applied ground simulation on the drag reduction is observed. The drag reduction of front and rear bogie fairings is valued similarly using a static ground, however on a moving ground the drag reduction of front bogie fairings is significantly increased. Good agreement between simulations and experiments is achieved.